Chronic pain: a long‐term sequela of epidermal necrolysis (Stevens–Johnson syndrome/toxic epidermal necrolysis) – prevalence, clinical characteristics and risk factors. (22nd September 2020) - Lefaucheur, J.‐P.; Valeyrie‐Allanore, L.; Ng Wing Tin, S.; Abgrall, G.; Colin, A.; Hajj, C.; de Prost, N.; Wolkenstein, P.; Ingen‐Housz‐Oro, S.; Chosidow, O.
Abstract: Background: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are associated with various sequelae. Chronic pain, one of these sequelae, has never been systematically evaluated. Objectives and methods: To assess the persistence of pain in a single‐centre cohort of 113 consecutive patients with SJS/TEN. From this cohort, 81 patients were interviewed more than 1 year after the initial episode and included in the study. Data were collected according to standardized questionnaires. Results: From the 81 interviewed patients, 52 patients (64%) were painless and 29 patients (36%) were painful. Chronic pain syndrome was associated with a more severe initial acute phase of the disease (larger extent of detachment, higher SCORTEN, increased rate of admission in ICU and complications, and longer hospital stay). Pain was mainly located at the level of eyes (55%), mouth and lower limbs (38–41%), with a moderate daily intensity on average (4.7/10). The 'affective' descriptors prevailed over the 'sensory' descriptors, with the exception of burning and itching sensations. Finally, regarding provoked pain, mechanical allodynia (to brushing and pressure) was more marked than thermal allodynia. Discussion: The persistence of chronic pain after SJS/TEN is a common phenomenon. Sensory descriptors are consistent with sensitization of both small‐diameter nerve fibres (burning and itching sensations) and large‐diameter nerve fibres (mechanical allodynia), but the affective‐emotional components of pain largely predominate. Conclusions: Complex mechanisms lead to persistent pain as long‐term sequela of SJS/TEN, among which mechanisms, psychological factors related to post‐traumatic stress disorder probably play a key role.